My Food Guide, Their Food Guide: diversity and personalization in Canada’s national dietary guidelines - Amend, Elyse (Cuizine, 2017)
Along with the release of Eating Well with Canada’s Food Guide in 2007, Health Canada introduced supplementary materials meant to tailor the general food guide to those not fully represented in it, and to account for dietary diversity. This article takes a closer look at one of these supplementary tools: the interactive food guide website, My Food Guide. It draws on transcripts and background documentation related to the 2007 food guide revision process, including the creation of the My Food Guide online tool, obtained through Access to Information requests that shed light on the issues that arose during its development. In addition to providing insight into how the My Food Guide website attempts to address cultural and dietary difference and the problems that arise, this article concludes by raising a number of questions researchers and policymakers might keep in mind as Health Canada prepares to release its upcoming revised dietary guidelines and related consumer resources.